Probiotic-Derived Polyphosphate Accelerates Intestinal Epithelia Wound Healing through Inducing Platelet-Derived Mediators - Shotaro Isozaki; Hiroaki Konishi; Mikihiro Fujiya; Hiroki Tanaka; Yuki Murakami; Shin Kashima; Katsuyoshi Ando; Nobuhiro Ueno; Kentaro Moriichi; Toshikatsu Okumura (Hindawi Limited, 2021)
Inflammatory bowel disease (IBD), such as ulcerative colitis (UC) and Crohn's disease (CD), is an intractable intestinal inflammation associated with the disruption of the intestinal mucosa. We previously demonstrated that Lactobacillus brevis-derived long-chain polyphosphate (poly P) improved the intestinal barrier function by the upregulation of cell adhesion and relieved intestinal inflammation, thereby exerting a curing effect on colitis in vitro, in vivo, and in an investigator-initiated clinical study of UC. However, how poly P improves mucosal defects induced by intestinal inflammation has not been elucidated. In this study, we detected the accumulation of platelets in inflamed tissues induced by poly P in a dextran sulfate sodium- (DSS-) induced colitis mouse model. A light transmission aggregometry analysis and scanning electron microscopy showed that poly P promoted the platelet aggregation. An SRB assay and ki-67 staining showed that the supernatant of poly P-treated platelet-rich plasma (PRP) increased intestinal epithelial cell growth. A wound healing assay showed that the supernatant of poly P-treated PRP, but not poly P itself, accelerated wound healing. A Western blotting analysis indicated that mitogen-activated protein kinase activation was induced by the supernatant of poly P-treated human PRP in the epithelial cells and its wound healing effect was significantly decreased by the inhibition of ERK signaling. These data suggested that platelet-derived mediators induced by poly P improved intestinal inflammation through the promotion of epithelial cell growth by the activation of the ERK signaling pathway. The mechanism is a novel host-microbe interaction through mammalian platelet-derived mediators induced by bacterial molecules.